Economic analysis of informal dairy processing units in Karnal district of Haryana - Thakur, Amit; Dixit, Anil Kumar; KM, Ravishankara (Indian Journal of Dairy Science, 2020)
Indian dairy sector is a blend of formal (cooperatives and private) and informal sector (small processing units, milk vendors etc.). Informal sector still dominates in terms of procurement of the sizeable milk surplus of the country. The present paper has examined the cost and return structure of informal dairy processing units in the Karnal district of Haryana. The net returns of these processing units are mainly attributed to varying level of milk handling capacity and diversification towards value added products. Dahi turned out to be most profitable with 53 per cent of profit over cost followed by ghee (12.75 %). The costs of dairy products were found to be decreasing with rising milk processing capacity. Solvency status of dairy processing units was found to be satisfactory yet there is a need for further strengthening.